Isolation of myricitrin and 3,5-di-O-methyl gossypetin from Syzygium samarangense and evaluation of their involvement in protecting keratinocytes against oxidative stress via activation of the Nrf-2 pathway - Sobeh, Mansour; Wink, Michael (Molecules, 2019)
The wax apple (Syzygium samarangense) is traditionally employed as an antibacterial and immunostimulant drug in traditional medicine. This plant is rich in different flavonoids and tannins. In this study, we isolated two compounds from S. samarangense leaves: myricitrin and 3,5-di-O-methyl gossypetin. Then, we investigated the mechanisms of action of the two compounds against oxidative stress (induced by sodium arsenite) and inflammation (induced by UV light) on human keratinocytes. We could clearly demonstrate that the pre-treatment of cells with both compounds was able to mitigate the negative effects induced by oxidative stress, as no alteration in reactive oxygen species (ROS) production, glutathione (GSH) level, or protein oxidation was observed. Additionally, both compounds were able to modulate mitogen-activated protein kinase (MAPK) signaling pathways to counteract oxidative stress activation. Finally, we showed that 3,5-di-O-methyl gossypetin exerted its antioxidant activity through the nuclear transcription factor-2 (Nrf-2) pathway, stimulating the expression of antioxidant proteins, such as HO-1 and Mn-SOD-3.
Gesehen am 20.08.2019